Central Asia and China relations: implications to India (Mongolian Journal of International Affairs, 2014)
No abstract available. DOI: http://dx.doi.org/10.5564/mjia.v0i10.120 The Mongolian Journal of International Affairs; Number 10, 2003, Pages 72-85